Assessment of the age-specific disability weight of chronic schistosomiasis japonica - Tie-Wu Jia; Xiao-Nong Zhou; Xian-Hong Wang; Jürg Utzinger; Peter Steinmann; Xiao-Hua Wu (The World Health Organization, 2007)
OBJECTIVE: To estimate the age-specific disability weight of chronic schistosomiasis japonica in China. METHODS: Between October 2004 and January 2005, residents from two schistosome-endemic counties were screened for Schistosoma japonicum infection using an enzyme-linked immunosorbent assay. Disability and morbidity were assessed in seropositive individuals using the European quality of life questionnaire with an additional cognitive dimension (known as the "EQ-5D plus") and ultrasonography. The age-specific disability weight of chronic schistosomiasis was estimated based on participants' self-rated health scores on the visual analogue scale of the questionnaire; the relationships between health status, morbidity and disability weight were explored using multilevel regression models. FINDINGS: Of 2843 seropositive individuals, 1419 (49.9%) were classified as having chronic schistosomiasis. Hepatomegaly was found in 76.3% (1082/1419); hepatic fibrosis was found in 73.3% (1040/1419); and splenomegaly was found in 18.6% (264/1419). Diarrhoea was the most common self-reported symptom (46.0%; 653/1419), followed by abdominal pain (32.6%; 463/1419), impaired capacity to work or study (30.7%; 436/1419), and blood in the stool (11.1%; 157/1419). More than half of the respondents reported impairments in at least one dimension of the EQ-5D plus questionnaire, particularly pain or discomfort (47.9%; 675/1410) and anxiety or depression (39.4%; 555/1410). The overall disability weight was 0.191, and age-specific weights ranged from 0.095 among those aged 5-14 years to 0.246 among those aged > 60 years. Multilevel regression models indicated that the disability weight was significantly associated with the participant's sex, grade of hepatic fibrosis, the presence of hepatomegaly, abdominal pain, blood in the stool, impaired capacity to work or study, and cognition. CONCLUSION: The disability weight attributable to chronic schistosomiasis japonica is high and increases with age. Our findings call for a reappraisal of the disability weights due to chronic schistosomiasis mansoni and schistosomiasis haematobia as well as a re-estimation of the global burden of schistosomiasis.